(untitled) (Research, Society and Development, 2020)
The guiding thread of this research is to analyze the discourses about the educational emptying process of the Basic Education Movement. The methodological theoretical approach that we use is the French Discourse Analysis (AD), which proposed a dialogue with three areas of scientific knowledge: linguistics, historical materialism and psychoanalysis. We understand that speech produces meaning effects and are materialized in language. Thus, all meaning is marked by ideological positions that are inserted in historical processes producing words, utterances and expressions. Discursive processes constitute a particular society. The discourse is not neutral, but ideological and marked by decision making by the subject. The documents that were analyzed are reports of the Movement of Basic Education (MEB), from 1964 to 1966, in addition the bibliographical research on the subject was performed. To carry out the analysis we use the categories of Production Conditions (broad and strict) to understand how the discourses reveal themselves, and their senses are going through this discourse. The results show a process of resistance of the MEB during the military regime that redirected its educational practices, although there was a process of political and educational emptying instituted by the military government.